1 ARCHIVES OF MARYLAND 77 (enacted 1639) (William Hand Browne ed., 1885) - (:unkn) unknown (General Publisher, 1639)
Required "every housekeeeper" to keep and bear one gun of "bastard muskett boare" design, bandeloors or shott bag, one pound of powder, four pounds of pistol or musket shot, sufficient quantity of matchlocks & flints, a sword, and belt.
--
Keywords: REQUIRED POSSESSION